Migrants or Expatriates? Americans in Europe - Koppenfels, Amanda Klekowski von. (Migration, Diasporas and Citizenship,, 2014)
This book examines the migration, integration and transnational activity of overseas Americans – American migrants – in France, Germany and the UK. It examines the reasons for their migration, introduces the concept of 'accidental migrant' and explores the question of overseas Americans' integration and identity formation.